Convergence with the reality of the body image term in mastectomised woman: reflexive analysis according to Barnum - Francisco Stélio Sousa; Marcos Venícios de Oliveira Lopes; Ana Fátima Carvalho Fernandes (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
The nursing theories have an important role in understanding the Nursing practice as a professional tool which brings autonomy and visibility. According to this, the elaboration of a reflexive theoretical study and analysis was chosen based on Barnum (1988) and targeted to develop researches to the adaptation process in mastectomised women. The main objective was the verification of the term Body Image as a convergence criterion with reality, elaborated by Roy in the Adaptation Model and having as corpus the Rodrigues dissertation (1999). Its possible to identify concepts that fit to the term proposed by Roy and Andrews (1999) and that integrate the study analysis of the adaptation process of mastectomised woman through stimulus, answers and adaptation levels in the mentioned phenomenon. Experiences like this lead an important theoretical deepening in nursing theories, making it able to accurate sights for a practical application.